High-intensity training and irisin response: A possible molecular cross-talk for irisin response - Ping Li; Ligang Tong; Xuecui Bi (Current Research in Physiology)
Physical exercise is widely recognized for its positive effect on health through alterations in genetic, molecular, or tissue-level pleiotropic effects. The extent of these advantages hinges on the intensity that elicits optimal threshold adaptation, facilitating interactions and communication within or between the cells. This requires the activation of several proteins, enzymes, and hormones. Irisin, an exercise-triggered hormone, is pivotal in converting white fat into brown fat, enhancing bone health, and optimizing brain functions. The activation of irisin is contingent upon precise exercise protocols that trigger several molecular cross-talks. However, no specific exercise protocols (types/intensity/duration) have been developed. Therefore, establishing specific exercise protocols could reveal irisin-induced benefits on bone and brain health. The present review discussed how high-intensity training (HIT) triggers the irisin response by activating its upstream and downstream molecular signaling pathways and how HIT helps to cross-talk these signaling pathways to improve irisin response.